ON SEVERAL KEY METHODOLOGICAL ISSUES OF PARLIAMENTARY GOVERNANCE - Simonyan, Tigran (Crisis Management and Technologies, 2025)
This article provides a comprehensive analysis of parliamentary governance and its various complexities. It explores different theoretical frameworks in political science, such as institutionalism, rational choice theory, pluralism, elite theory, democratic theory, and social choice theory, which help scholars to understand how parliamentary systems operate. The paper discusses how these theories apply to understanding the legislative process, the behavior of political actors, and the impact of parliamentary decisions. Furthermore, the article addresses challenges in conceptualizing and measuring parliamentary effectiveness, considering factors such as political context, party systems, and external influences. It also examines the role of party systems and party discipline in shaping parliamentary dynamics, highlighting the differences between multi-party, two-party, and dominant-party systems. Simultaneously the article looks to the qualitative and quantitative approaches used in the political science to examine and study how the effectiveness of the parliamentary system can be measured. In the end, the article touches upon the role of media in shape of public discourse.